(untitled) - Ongeri, Sandrine; Crousse, Benoît (Comptes Rendus. Chimie)
This account summarizes our work on the synthesis of fluorinated peptidomimetics integrating the N-CF2R triazole functions. Emphasis is placed on the development of fluorinated foldamers possessing preferential conformations. We have shown that these foldamers are potential modulators of amyloid protein aggregation.